2023
DOI: 10.3390/su15108070
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Power of Connection: How Adolescents’ Prosocial Propensity Drives Ecological and Altruistic Behaviours

Abstract: Both altruistic and ecological behaviours are considered prosocially driven behaviours, but our understanding of what motivates action in either the human or ecological domain is still in its infancy. Our goal was to assess connection to nature, connection to people, and connection to country as mediators of the relationship between prosocial propensity and prosocial behaviours in both the ecological and human domains. This study used honesty-humility as an indicator of prosocial propensity. Data for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…However, the studies by Ernst et al [10] and Krettenauer [56] reveal no significant link between feeling morally obliged to act in pro-environmental ways and adolescents' PEB. For connectedness with nature, all other studies suggest that having contact with nature, feeling an emotional connection with nature (e.g., being part of the natural world), and feeling empathetic towards living beings, is associated with PEB in adolescence [12,51,53,56,57,62,82,87]. For climate change concern, adolescents who are worried about climate change also adopt more PEB [43,49,58,77,79,81].…”
Section: Individual Correlatesmentioning
confidence: 98%
“…However, the studies by Ernst et al [10] and Krettenauer [56] reveal no significant link between feeling morally obliged to act in pro-environmental ways and adolescents' PEB. For connectedness with nature, all other studies suggest that having contact with nature, feeling an emotional connection with nature (e.g., being part of the natural world), and feeling empathetic towards living beings, is associated with PEB in adolescence [12,51,53,56,57,62,82,87]. For climate change concern, adolescents who are worried about climate change also adopt more PEB [43,49,58,77,79,81].…”
Section: Individual Correlatesmentioning
confidence: 98%
“…Within an environmental domain, research has shown openness to experience and extraversion may be the most significant personality predictors of pro-environmental behavior (Brick & Lewis, 2016;Markowitz, Goldberg, Ashton & Lee, 2012). Interestingly, more recent research (Duong & Pensini, 2023;Neaman, Montero, Pensini et al, 2023;Neaman, Pensini, Zabel et al, 2022;Otto, Pensini, Zabel et al, 2021) has positioned honesty-humility as an important personality predictor in the environmental domain. The latter is consistent with findings pertaining to prosocial behavior toward humans, where Thielmann, Spadaro, and Balliet's (2020) recent meta-analysis has demonstrated that of eight broad and 43 narrow personality predictors, Ashton and Lee's (2007) honestyhumility trait from the HEXACO model of personality predicted prosocial behavior above and beyond all other broad personality constructs.…”
Section: Prosocial Propensitymentioning
confidence: 99%